Morphology‐Reserved Synthesis of Discrete Nanosheets of CuO@SAPO‐34 and Pore Mouth Catalysis for One‐Pot Oxidation of Cyclohexane. Issue 7 (9th January 2020) - Guo, Xiangke; Xu, Mengxia; She, Minyi; Zhu, Yan; Shi, Taotao; Chen, Zhaoxu; Peng, Luming; Guo, Xuefeng; Lin, Ming; Ding, Weiping
Abstract: Discrete nanosheets of silicon‐doped AlPO4 molecular sieves (SAPO‐34) with a thickness of ≈7 nm have been prepared through morphology‐reserved synthesis with a lamellar aluminum phosphate as precursor. Cages of the nanosheets are in situ incorporated with copper oxide clusters. The CuO@SAPO‐34 nanosheets exhibit a large external surface area with a high number of (010) channel pores on the surface. Due to the thin morphology, copper oxide clusters occupy the outmost cages with a probability >50 %. The distinctive configuration facilitates a new concept of pore mouth catalysis, i.e., reactant molecules larger than the pores cannot enter the interior of the molecular sieves but can interact with the CuO clusters at "the mouth" of the pore. In heterogeneous catalysis, CuO@SAPO‐34 nanosheets have shown top performance in one‐pot oxidation of cyclohexane to adipic acid by O2, a key compound for the manufacture of nylon‐66, which is so far produced using non‐green nitric acid oxidation. Abstract : Like at the dentist : 2D and super‐thin CuO@SAPO‐4 nanosheets with ≈7 nm thickness and single crystalline structure have been synthesized. The nanosheets show excellent catalytic performance for the selective oxidation of cyclohexane to adipic acid using O2 as oxidant through a pore mouth catalysis mechanism.